Learning curve of ovarian cystectomy by vaginal natural orifice transluminal endoscopic surgery: a cumulative sum analysis - Tan, Kailiang; Wei, Liufei; Deng, Zengmei; Yao, Desheng; Jiang, Li (Frontiers in Medicine, 2024)
Purpose To identify the learning curve in ovarian cystectomy by vaginal natural orifice transluminal endoscopic surgery. Methods Data consist of consecutively ordered patients who underwent ovarian cystectomy via vaginal natural orifice transluminal endoscopic surgery between May 2020 and June 2023. The learning curve of ovarian cystectomy via vaginal natural orifice transluminal endoscopic surgery was measured in terms of the operating time adjusted by multivariate linear regression. A cumulative sum analysis was performed to establish the learning curve. Patients’ characteristics and surgical outcomes were compared based on the inflection points of this curve. Results The learning curve was divided into two unique phases: phase 1 (1–26 patients), and phase 2 (27–40 patients). The expected operating time in phase 2 was shorter than in phase 1 (86.4 ± 11.2 min vs. 102.0 ± 22.7 min, p = 0.021). The time to first postoperative flatus was shorter in phase 2 compared with phase 1 (14.6 ± 6.5 h vs. 20.6 ± 6.3 h, respectively, p = 0.008). No significant differences were observed in terms of patient’s age, BMI, tumor size, parity, bilateral ovarian tumor, pathological diagnoses, estimated blood loss, postoperative pain score, or perioperative complications between the two phases. Conclusion Proficiency in ovarian cystectomy by vaginal natural orifice transluminal endoscopic surgery was achieved after 26 surgeries based on cumulative sum analysis. These findings may provide insight for structured training programs of ovarian cystectomy via vaginal natural orifice transluminal endoscopic surgery.